Synthesis, structural characterization and photophysical properties of highly photoluminescent crystals of Eu(III), Tb(III) and Dy(III) with 2,5-thiophenedicarboxylate - Marques, Lippy F.; Cantaruti Júnior, Anderson A.B.; Ribeiro, Sidney J.L. [UNESP]; Scaldini, Felipe M.; Machado, Flávia C. (Elsevier, 2013)
Lanthanide compounds of general formula [Ln2(2,5-tdc) 3(dmf)2(H2O)2] ·2dmf·H2O (Ln = Eu(III) (1), Tb(III) (2), Gd(III) (3) and Dy(III) (4), dmf = N,N′-dimethylformamide and 2,5-tdc2- = 2,5-thiophedicarboxylate anion) were synthesized and characterized by elemental analysis, X-ray powder diffraction patterns, thermogravimetric analysis and infrared spectroscopy. Phosphorescence data of Gd(III) complex showed that the triplet states (T1) of 2,5-tdc2- ligand have higher energy than the main emitting states of Eu(III), Tb(III) and Dy(III), indicating that 2,5-tdc2- ligand can act as intramolecular energy donor for these metal ions. An energy level diagram was used to establish the most relevant channels involved in the ligand-to-metal energy transfer. The high value of experimental intensity parameter Ω2 for the Eu(III) complex indicate that the europium ion is in a highly polarizable chemical environment. The emission quantum efficiency (η) of the 5D0 emitting level of Eu(III) was also determined. The complexes act as possible light conversion molecular devices (LCMDs). © 2013 Elsevier B.V. All rights reserved.
Keywords: Photoluminescence 2,5-Thiophenedicarboxylic acid Lanthanides